Legal Personhood for Artificial Intelligence: Pro, Contra, Abstain? - Militsyna, Kateryna (Teisė, 2022)
This article is about the legal personhood of artificial intelligence as one of the existing options of regulating AI and coping with the challenges arising out of its functioning. It begins with the search for the definition of AI and goes on to consider the arguments against the legal personhood of AI, the options of such a legal personhood, and the factors taken into account in devising the legal personhood of AI. The article ends with our vision of the legal personhood of AI.
Keywords: artificial intelligence; legal personhood; electronic personhood; civil law